Redox Imbalance in Neurological Disorders in Adults and Children - Federica Rey; Clarissa Berardo; Erika Maghraby; Alessia Mauri; Letizia Messa; Letizia Esposito; Giovanna Casili; Sara Ottolenghi; Eleonora Bonaventura; Salvatore Cuzzocrea; Gianvincenzo Zuccotti; Davide Tonduti; et al. (MDPI AG, 2023)
Oxygen is a central molecule for numerous metabolic and cytophysiological processes, and, indeed, its imbalance can lead to numerous pathological consequences. In the human body, the brain is an aerobic organ and for this reason, it is very sensitive to oxygen equilibrium. The consequences of oxygen imbalance are especially devastating when occurring in this organ. Indeed, oxygen imbalance can lead to hypoxia, hyperoxia, protein misfolding, mitochondria dysfunction, alterations in heme metabolism and neuroinflammation. Consequently, these dysfunctions can cause numerous neurological alterations, both in the pediatric life and in the adult ages. These disorders share numerous common pathways, most of which are consequent to redox imbalance. In this review, we will focus on the dysfunctions present in neurodegenerative disorders (specifically Alzheimer's disease, Parkinson's disease and amyotrophic lateral sclerosis) and pediatric neurological disorders (X-adrenoleukodystrophies, spinal muscular atrophy, mucopolysaccharidoses and Pelizaeus-Merzbacher Disease), highlighting their underlining dysfunction in redox and identifying potential therapeutic strategies.